2005
DOI: 10.1111/j.1365-2958.2005.04938.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of the type I secreted α‐haemolysin via outer membrane vesicles from Escherichia coli

Abstract: SummaryThe α α α α -haemolysin is an important virulence factor commonly expressed by extraintestinal pathogenic Escherichia coli . The secretion of the α α α α -haemolysin is mediated by the type I secretion system and the toxin reaches the extracellular space without the formation of periplasmic intermediates presumably in a soluble form. Surprisingly, we found that a fraction of this type I secreted protein is located within outer membrane vesicles (OMVs) that are released by the bacteria. The α α α α -haem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
107
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 53 publications
13
107
0
3
Order By: Relevance
“…Because RTX toxins are transported through the bacterial cell envelope without a periplasmic intermediate (Gray et al, 1986;Koronakis et al, 2004), LtxA would have to be exported through TdeA before localizing to the outer membrane or within vesicles. Observations about LtxA localization fit the model proposed by Balsalobre et al (Balsalobre et al, 2006), who recently reported that E. coli α -hemolysin localization to outer membranederived vesicles occurs upon assembly of the complete type I secretion machinery.…”
Section: Discussionsupporting
confidence: 83%
“…Because RTX toxins are transported through the bacterial cell envelope without a periplasmic intermediate (Gray et al, 1986;Koronakis et al, 2004), LtxA would have to be exported through TdeA before localizing to the outer membrane or within vesicles. Observations about LtxA localization fit the model proposed by Balsalobre et al (Balsalobre et al, 2006), who recently reported that E. coli α -hemolysin localization to outer membranederived vesicles occurs upon assembly of the complete type I secretion machinery.…”
Section: Discussionsupporting
confidence: 83%
“…In gram-negative bacteria, several functions have been attributed to the release of outer membrane vesicles such as DNA and protein secretion, cell to cell communication and a stress response to cell envelope damage. For example, the a-hemolysin toxin of Escherichia coli is released in association with outer membrane vesicles (Balsalobre et al 2006), while denatured proteins at the cell envelope are expelled from the cell via outer membrane vesicles (McBroom and Kuehn 2007). Outer membrane vesicles produced by Pseudomonas aeruginosa are equipped with antimicrobial activity and have been implicated in quorum sensing allowing individual cells to act as a group (Mashburn and Whiteley 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Via MVs, bacteria can expose host cells to relatively high concentrations of toxins and additional virulence factors without the requirement of a close contact between the bacterial and target mammalian cells (2)(3)(4)(5)(6)(7)(8)(9). MVs have also several defensive functions, including a role in antimicrobial peptide resistance (6,10).…”
mentioning
confidence: 99%